Kerusakan Bulir Padi dan Keragaman Parasitoid Telur Hama Walang Sangit di Kabupaten Aceh Utara, Propinsi Aceh: Damage of Rice Grains and Parasitoid Diversity of Rice Ear Bug Eggsin North Aceh Regency, Aceh Province - Hendrival Hendrival; Irham Irham; Muhammad Muaz Munauwar; Novita Pramahsari Putri; Nurmasyitah Nurmasyitah (Universitas Widya Gama Mahakam, 2024)
The rice ear bug is a potential pest that damages rice grains. This pest damages rice grains when they reach the flowering phase until they are ripe for harvest. Egg parasitoid species can control rice ear bugs in the early stages of life. The research aims to calculate the percentage of attacks by rice ear bugs and explore the diversity of their egg parasitoids in the lowland rice agroecosystem in North Aceh Regency, Aceh Province. Purposive random sampling was used to determine the sampling location. Observations and sampling were carried out based on the stages of rice grain maturity, namely milk stage of rice (63–70 days), yellow-ripe (71–77 days), full ripe (78–84 days), and harvest ripe (85–91 days). Egg sampling was carried out in each sample plot of 50 groups of eggs. The results showed that damage to rice grains at all stages of grain maturity was relatively light, namely 0.6–17.6%. There were two species of egg parasitoids found, namely Hadronotus leptocorisae (Scelionidae) and Ooencyrtus malayensis (Encyrtidae). The species diversity index was low, while the species evenness index was high. The H. leptocorisae species is one of the dominant egg parasitoids with parasitization levels reaching > 50% at the milky and yellow-ripe stages